Антибактеріальна терапія у хворих на сепсис - Шаповал, Сергій Дмитрович; Shapoval, S. D. (My University, 2024)
На сьогодні, на долю сепсису, причиною якого є гнійно-запальні процеси м’яких тканин, приходиться понад 45% випадків. У більшості багатопрофільних лікарень частота грампозитивного і грамнегативного сепсису приблизно однакова. Антибактеріальна терапія (АБТ) є найважливішим компонентом комплексної терапії сепсису, а рання адекватна емпірична АБТ призводить до зменшення летальності та частоти ускладнень. Антибіотики у хворих на сепсис повинні призначатися терміново після уточнення діагнозу та до отримання результатів бактеріологічного дослідження. Швидка інтерпретація важкості інфекційного процесу може бути виконана за допомогою діагностичних критеріїв сепсису ACCP/SCCM, критеріїв органної дисфункції (gSOFA, SOFA, MODS) або експрес-тесту на вміст прокальцитоніну. Мікробіологічна діагностика сепсису є головною при призначенні адекватних режимів АБТ. У тому випадку, коли із ймовірного осередку інфекції та із периферичної крові виділяється один і той же мікроорганізм, його етіологічну роль у розвитку сепсису слідує рахувати доказовою. Стандартом дослідження крові на стерильність є забір матеріалу із двох периферичних вен із інтервалом до 30 хвилин, при цьому із кожної вени кров потрібно набирати у два флакони. Не допустимо брати кров із катетера! Побудова алгоритму АБТ з урахуванням етіології та особливостей резистентності мікроорганізмів до антибактеріальних препаратів є самим оптимальним підходом. На сьогодні оптимальним режимом емпіричної АБТ важкого нозокоміального сепсису з ПОН є карбапенеми – як препарати, що мають найбільш широкий спектр дії і до яких спостерігається найменший рівень резистентності серед внутрішньо – лікарняних штамів грам-бактерій. В деяких випадках альтернативою карбапенемів є цефепім, цефтаролін, захищені антипсевдомонадні β-лактами (цефаперазон/сульбактам, піперацилін/тазобактам) та “респіраторні” фторхінолони. У випадках неефективності зазначенних режимів АБТ слід оцінити доцільність додаткового призначення глікопептидів (ванкоміцин, тейко-планін або лінезолід, а також системних антимікотиків (флуконазол). Останні також повинні призначатися після 7-10 діб після початку АБТ у профілактичній дозі 150 мг на тиждень. Today, sepsis, the cause of which is purulent-inflammatory processes of soft tissues, accounts for more than 45% of cases. In most multidisciplinary hospitals, the frequency of gram-positive and gram-negative sepsis is approximately the same. Antibacterial therapy (ABT) is the most important component of the complex therapy of sepsis, and early adequate empiric ABT leads to a decrease in mortality and the frequency of complications. ABT of sepsis at the beginning of treatment, in most cases, is empirical in nature, but it should be remembered that taking the material for microbiological research must be done before the start of antibacterial therapy! According to the principles adopted in the guide-line "Sepsis - 3", the use of antibiotics for the treatment of sepsis is a necessary component, the effectiveness of which cannot be doubted. It should be remembered that a delay in the appointment of an antibacterial drug to patients with sepsis and septic shock for 1 hour leads to an increase in the risk of death of the patient by 7,6%. Empiric ABT should be initiated with a broad-spectrum regimen of one or more antibiotics in patients with sepsis or septic shock to cover all possible pathogens (including bacterial, possibly fungal, or viral). Empiric ABT should be narrowed after identification of the pathogen and determination of its sensitivity and/or when adequate clinical improvement is registered. There are no indications for long-term systemic antibacterial prophylaxis in patients with severe forms of inflammatory conditions of non-infectious origin (for example, severe pancreatitis, burns). Measurement of procalcitonin levels can be used to shorten the duration of anti-bacterial therapy in patients with sepsis. Rapid interpretation of the severity of the infectious process can be performed using ACCP/SCCM sepsis diagnostic criteria, organ dysfunction criteria (gSOFA, SOFA, MODS) or rapid procalcitonin test. Microbiological diagnosis of sepsis is the main factor in prescribing adequate ABT regimens. In the case when the same microorganism is released from the probable source of infection and from the peripheral blood, its etiological role in the development of sepsis should be considered as evidential. The standard for testing blood for sterility is the collection of material from two peripheral veins with an interval of up to 30 minutes, while blood from each vein must be collected in two vials. It is not permissible to take blood from the catheter! Building an ABT algorithm taking into account the etiology and characteristics of resistance of microorganisms to antibacterial drugs is the most optimal approach. Тoday, the optimal regimen of empiric ABT of sepsis with PON is carbapenems - as drugs that have the widest spectrum of action and to which the lowest level of resistance is observed among intra-hospital strains of gram(-) bacteria. In some cases, an alternative to carbapenems is cefepime, ceftaroline, protected by antipseudomonas β-lactams (cefaperazone/sulbactam, piperacil-lin/tazobactam) and "respiratory" fluoroquinolones. In cases of ineffectiveness of the indicated regimens of ABT, the feasibility of additional appointment of glycopeptides (vancomycin, teicoplanin or linezolid), as well as systemic antimycotics (fluconazole) should be evaluated. The latter should also be prescribed after 7-10 days after the start of ABT in a prophylactic dose of 150 mg per week.
Antibacterial therapy in sepsis patients
Keywords: сепсис; септичний шок; антибактеріальна терапія; резистентність; летальність; sepsis; septic shock; antibacterial therapy; resistance; lethality